Pediatric vaccines and vaccinations : a European textbook - Vesikari, Timo; Van Damme, Pierre (Springer, 2017)
This graduate textbook serves as a highly readable guide on vaccines and vaccination in infants, children and adolescents from an European perspective. The first part of the book is dedicated to childhood and adolescent vaccine schedules, maternal and neonatal immunization and safety of vaccines. In a second part we focus on viral and bacterial vaccines. Further chapters discuss pediatric travel vaccines, vaccines in the pipeline and the European registration process. This book is intended to be a reference textbook and will help to standardize the information on vaccines and immunization program in the WHO European Region.